Family Etiquette of Kumyks of 19th - Early 20th Centuries - K. M. Kramynina (Научный диалог)
The article considers the family etiquette of Kumyks of 19th - early 20th centuries on the basis of existing scientific works devoted to the life of Caucasus peoples, and expedition material collected by the author of the article. Various aspects of intra-family etiquette relationships of Kumyks in the specified period are shown. Various etiquette situations, roles and statuses of each family member are recreated and analyzed in detail. The question is raised about the conditionality of the relations of supremacy and unquestioning subordination of one family member to another within the framework of etiquette and observance of mandatory norms of behaviour. The relevance of this study is due to the interest in the identity of family relations of different peoples against the background of globalization processes, often devaluing the role of the family. It is indicated that the culture of behaviour, in particular etiquette relations, are based on ethical norms that have been formed in society and in the family as part of it for centuries. This study examines the family relationships in Kumyks, which are regulated by certain etiquette rules. Particular attention is paid to family etiquette in various forms of the family - large (undivided) ( уллу агълю - in Kumyk language) and small (nuclear) ( бир уьй агълю - in Kumyk language) that existed in the study period in Kumyks.